2004
DOI: 10.1007/s10024-003-3025-6
|View full text |Cite
|
Sign up to set email alerts
|

MALT Lymphoma in Children: Case Report and Review of the Literature

Abstract: Mucosa-associated lymphoid tissue (MALT) lymphoma predominantly occurs in adults, and is rare in children. We report a case of MALT lymphoma involving minor salivary gland of the lip in an otherwise healthy 12-year-old boy. This is the second case report of MALT lymphoma of minor salivary gland in an immunocompetent child. Of 24 cases of MALT lymphomas in children reported in the English literature, parotid MALT lymphomas in human immunodeficiency virus (HIV) patients and H. pylori infection-associated gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 29 publications
(31 reference statements)
0
33
0
Order By: Relevance
“…Other risk factors for MALT lymphoma include autoimmune diseases like Hashimoto thyroiditis or Sjogren syndrome, and Borrelia burgdorferi for skin lymphoma. A further prerequisite for the development of MALT lymphoma in children may be the presence of HIV infection [17,18]. In some patients no risk factors can be identified.…”
Section: Discussionmentioning
confidence: 97%
“…Other risk factors for MALT lymphoma include autoimmune diseases like Hashimoto thyroiditis or Sjogren syndrome, and Borrelia burgdorferi for skin lymphoma. A further prerequisite for the development of MALT lymphoma in children may be the presence of HIV infection [17,18]. In some patients no risk factors can be identified.…”
Section: Discussionmentioning
confidence: 97%
“…MALT often develops within the context of a pre-existing inflammatory response due to infection or to autoimmune disorder. Many studies show the relationship between H. pylori infection and gastric MALT lymphoma (Isaacson & Whright, 1984;Kurugoglu et al, 2002); some authors have reported a regression of MALT lymphoma in parotid gland (Alkan et al, 1996), lip gland (Berrebi et al, 1998), small intestine (Fischbach et al, 1997) Mo et al, 2004). In some patients no risk factors can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…These lymphomas arise mostly in the gastrointestinal tract and are associated with Helicobacter pylori [41]. A clonal evolution within the B-cell population in response to the infectious process is hypothesized to lead an indolent MALT lymphoma [42]. The long evolution is believed to be a reason for the rarity of MALT lymphomas in children [43].…”
Section: Marginal Zone Lymphomamentioning
confidence: 99%
“…The long evolution is believed to be a reason for the rarity of MALT lymphomas in children [43]. MALTs may be due to longstanding chronic infections with H. pylori in stomach lymphomas, Borrelia burgdorferi in skin lymphomas, HIV infection, or autoimmune diseases [42]. MALT lymphomas are morphologically heterogenous.…”
Section: Marginal Zone Lymphomamentioning
confidence: 99%